The poetic image in the book of Al-Amali by Abu Ali Al-Qali - Salim Mnaty, Researcher. Ruweida; Abdul Nabi Al-Shawi , Prof. Dr. Murtadha (Basra studies journal, 2023)
The artistic Image is the most Important rule of poetic construction, as It is the aesthetic and psychological formation of the poem. The scenes accompanied the poet within his life have profound effects on his conscience, so these feelings flow in tangible and aesthetic formulations accompanied by an emotion that the same recipient responds to automatically. To understand those emotions and feelings that the recipient responded to the poet inimitable artistic and poetic geniuses can be done by linking Imagination with the Image.